The maximum amplitude weighted integrated energy spectra: A new gauge in seismic thin-bed interpretation - Purnomo, E.W. (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Some combinations of seismic attributes are superior in detecting thinbed thickness from 3D seismic data. However, their physical unit or meaning can be difficult to determine. Such attributes are considered as relative values. This paper introduces a newly developed relative-value attribute, which was identified to be more sensitive in detecting seismic thin-bed structures. The new attribute was developed based on seismic frequency shifting and amplitude decrease phenomena that occur when the seismic wave responds to a thinning bed structure. The new attribute is constructed by multiplying the integrated energy spectra with the relative maximum amplitude. Through a wedge model seismic test it was shown that the new relative-value attribute consistently gave more proportional and linear responses to the thin-bed thickness. The new attribute was examined in delineating a channel structure on the basis of public 3D seismic data from Stratton Field, Texas USA and the Group F Reservoir in the Malay Basin, Malaysia. The new attribute delineated the meandering channels featured in those two fields very well. Â© 2015 Published by ITB Journal Publisher.